Les tableaux vivants à Venise au tournant du XXe siècle : l’histoire d’un passe-temps mondain retracée dans le journal de Lady Layard - Cazzola, Alice (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2019)
This article examines the iconographic program and social function of the tableaux vivants performed by the AngloAmerican intellectual elite resident in Venice at the turn of the twentieth century. It considers the highly esteemed tableaux performed at Ca’ Cappello between 1888 and 1910 through a reading of the journals of the society hostess Lady Layard (1843–1912). The annual Christmas tableaux vivants took place amid a vibrant salon culture fostered by wealthy Anglophones and drew inspiration from both the Renaissance and Carnival heritage of Venice as well as the British tradition of Christmas pantomime and masquerade. While the iconography of the tableaux vivants points to the connoisseurship and aesthetic tastes of this elite, the ambiguous status of this art form on the boundary of fine arts and popular culture leads to an examination of the tableaux’s social function and of their performers’ cultural consciousness.